Shaykh Abdullah Fahim's Views on Salawat in a Psychological Perspective - Khairul Nizam bin Zainal Badri (Psikoislamika: Jurnal Psikologi Islam, 2021)
Abstract: Psycho-religion is classified as the highest spiritual psychotherapy in the field of psychology. This is because the field involves religion that works to increase confidence thus speeding up the healing process. One of the therapies that fall into this category is the practice of reciting Salawat. This practice is common in traditional institutions of learning institutions in the Malay world. In some places, this practice becomes part of the curriculum of study. Some recite it as remembrance, and some recite it in the form of melodic performances such as qasidah, hadrah and so on. This study, however, is limited to the views of prominent educators in Malaya, Shaykh Abdullah Fahim (1869 - 1961) to practice reading the Salawat. The main objective of this study is to look at Shaykh Abdullah Fahim's thoughts on Salawat from a psychological perspective. This study uses a fully qualitative method. For data collection purposes, an archival approach was used. The conclusion of the study was made by using an inductive approach that is by summarizing the findings in general. The study found that the practice of Salawat from the point of view of Shaykh Abdullah Fahim has potential development benefits in terms of emotions, behaviour, and motivation.Keywords: Shaykh Abdullah Fahim; Salawat; psycho-religion; psychologyAbstrak: Psikoreligius tergolong psikoterapi spiritual tertinggi dalam bidang psikologi psikoterapi. Hal ini dikarenakan bidang tersebut melibatkan agama yang berfungsi untuk meningkatkan kepercayaan diri sehingga mempercepat proses penyembuhan. Salah satu terapi yang termasuk dalam kategori ini adalah praktik membaca salawat. Praktik ini sudah menjadi tradisi di lembaga-lembaga lembaga pembelajaran tradisional di dunia Melayu. Di beberapa tempat, praktik ini menjadi bagian dari kurikulum studi. Ada yang membacanya untuk dzikir, dan ada pula yang membacanya dalam bentuk sesajen seperti qasidah, hadrah dan sebagainya. Namun penelitian ini terbatas pada pandangan tokoh pendidik di Malaya, Syekh Abdullah Fahim (1869 – 1961) tentang amalan membaca salawat. Tujuan utama dari penelitian ini adalah untuk melihat pemikiran Syekh Abdullah Fahim tentang salawat dari perspektif psikologis. Penelitian ini menggunakan metode kualitatif penuh. Untuk tujuan pengumpulan data, pendekatan arsip digunakan. Kesimpulan penelitian dibuat dengan menggunakan pendekatan induktif yaitu dengan meringkas temuan secara umum. Studi ini menemukan bahwa praktik salawat dari sudut pandang Syekh Abdullah Fahim memiliki potensi manfaat pengembangan dalam hal emosi, perilaku, dan motivasi.Kata Kunci: Shaykh Abdullah Fahim; salawat; psiko-religius; psikologi